ANALISIS JAMUR KHAMIR DAN JAMUR PENICILLIUM PADA MINUMAN SUSU KEMASAN DAN SUSU SEGAR YANG BEREDAR DI KOTA MEDAN TAHUN 2015 - nurma irama; taufik ashar; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Milk is a food that has a high nutritional value, but are easily damaged. Sp penicilium presence of mold and yeast in a beverage can endanger the health of consumers. This can lead to food poisoning and drinks. The purpose of this study was to determine the presence of Penicillium fungi and yeast as well as to determine the physical characteristics of the milk include color, smell and taste of milk in the milk beverage packaging and fresh milk which is circulated in Medan in 2015. This study was a descriptive type. The data collected was obtained from the results of tests carried out in the Laboratory of Microbiology Department of Biology, Faculty of Mathematics and Natural Sciences USU. Samples were 8 types of packaging milk and 2 types of fresh milk in circulation in the city of Medan in 2015. Data analysis was performed by analysis of frequency distribution that states the research object under study. Based on laboratory test results, three of the eight positive samples containing the fungal yeast. Two samples of which were sweetened condensed milk packaged in cans and plastic sachets. While the other sample is UHT milk in plastic bottles. Based on the results of laboratory tests on fresh milk, not the discovery of either fungus penicillium fungi and yeasts. Suggestions from this study is the Importance of cooperation with BPOM to conduct socialization to milk producers shall include the date of expiration, For the milk producers, should be maintaining the quality of milk produced. For consumers, should pay attention to the expiration date and the condition of the packaging of dairy products to be consumed. To further research, it is advisable to do some research using variables more varied. Keywords: Penicillium, yeast, milk.